Increasing The Use Of Continuous Erythropoietin Receptor Activators To Correct Anemia In Maintenance Hemodialysis Patients.: Reprinted for our readers interest originally published PJKD 2018;2(4):9-11. (Pakistan Journal of Kidney Diseases, 2021)
This article reviews the role of the Continuous Erythropoetin Receptor Activators (CERAs) in the management of anemia in the dialysis population. Despite the convenience of once per month dosage frequency instead of the twice per week conventional erythropoetin stimulators, CERAs have struggled to achieve universal acceptance. This article sheds light on the reasons and fairness of this choice.